Ochrona granicy państwowej przed nielegalnymi ucieczkami przez Wydział II Kaszubskiej Brygady Wojsk Ochrony Pogranicza w latach 1980–1983. Procedury i metody działania - Kłodziński, Marcin (Pamięć i Sprawiedliwość, 2012)
The exceptionally turbulent years 1980–1983 made many people decide to flee Poland. One of the main obstacles in their way were the counter-intelligence structures of WOP (Border Defence Troops). Among them, the 2 nd Department of the Kashubian WOP Brigade in Gdańsk. The Department applied a very extensive range of methods to protect the state border. Special emphasis was put on preventive actions. Apart from bordercontrols, i.a. operational activities were applied against persons suspected of intending to flee the country. Functionaries of the 2 nd Department subjected them to surveillance, exercised, among other, by the border units’ network of secret agents. It also included actions aimed at reducing to the minimum the potential escapee’s contacts with the border zone, what could seriously complicate the lives ofpersons professionally dependent on that area, cutter fishermen for example.The work of the functionaries of the 2 nd Department of the Gdańsk Brigade of WOP extended beyond purely preventive issues. Provided with competence proper for investigative services, they also handled cases of escapes as such, both accomplished and prevented. Suspects and witnesses were subjected to multiple interrogations lasting many hours, often combined with confrontations. If necessary, also home searches and on-site inspections were carried out. Investigations were very meticulous, applying not only to escapees. The 2 nd Department officers’ scrutiny also extended to persons that could be suspected of offering whatever form of assistance, factual or alleged, at illegal border crossing. Repressive measures were often applied against them, without proving guilt beforehand.The actions undertaken by the 2 nd Department towards the escapees, did not change after the formal end of martial law in July 1983. The character of service did not allow for any modifications of applied methods, that remained in continuous use until 1989.